Morinda lucida Aqueous Stem Bark Extract Ameliorates Hepato-Renal Dysfunctions in Experimental Diabetes Model (Nigerian Journal of Physiological Sciences, 2019)
Summary: Diabetes Mellitus (DM) is a leading pan-systemic endocrine disorder with attendant high morbidity and mortality owing to its deleterious effects on vital body organs caused by untreated chronic hyperglycemia, attendant oxidative stress and glycation processes. The present study is designed to investigate possible protective role and mechanism(s) of action of 125-500 mg/kg/day of Morinda lucida aqueous stem bark extract (MLASE) on renal and hepatic functions in alloxan-induced hyperglycemic rats for 8 days. Forty-two alloxan-induced hyperglycemiic male Wistar rats were randomly allotted to Groups II-VI and orally treated with 10 ml/kg/day distilled water, 5 mg/kg/day glibenclamide, 125 mg/kg MLASE, 250 mg/kg MLASE, and 500 mg/kg/day MLASE, respectively. Group I normal rats served as untreated control and were orally treated with 10 ml/kg of distilled water, all under same sham-handling. Blood samples were taken for measurement of fasting blood glucose, renal and hepatic function profile. Liver and kidney tissue samples were taken for determination of the activities of oxidative stress markers such as malondialdehyde (MDA), reduced glutathione (GSH), and glutathione peroxidase (GPx), catalase (CAT) and superoxidase dismutase (SOD). Results showed that intraperitoneal injection with 120 mg/kg of alloxan in cold 0.9% normal saline reliably and significantly induced a steadily sustained hyperglycemia which were ameliorated by short-term oral treatment with 125-500 mg/kg/day of MLASE, dose dependently, similar to that ameliorated by the standard antihyperglycemic drug, glibenclamide. Similarly, MLASE significantly mitigated against derangements in the measured renal and hepatic function parameters as well as oxidative stress induced by alloxan-induced hyperglycemia. In conclusion, results of this study showed the protective role of 125-500 mg/kg/day of MLASE in chronic hyperglycemia-associated renal and hepatic dysfunctions which was mediated via antioxidant and free radical scavenging activities of MLASE